Feminist perspective on autonomy in the context of local public policies. The case of the Municipality of Santa Fe (2011-2019) (Papeles, 2023)
This article critically analyzed how local governments have gained relevance in the last decades. Gender issues have been of paramount importance within the new requirements in recent years and municipalities have been forced to adjust to the new demands that have emerged. This paper examines how José Corral’s government (2011-2015 and 2015-2019) responded to demands not only from a human rights perspective but also considering the gender criteria. The autonomy of women is a central concept in this government.To conclude, this article aims to analyse the concept of autonomy and its impact on public policies between 2011 and 2019 from a gender perspective.
Keywords: Feminist autonomy; local government; gender; public policies; municipal management